Biomechanical analysis of fencing techniques: Insights from motion capture and analysis - Jia, Y. (Journal of Physical Education, 2025)
This work explores the biomechanical characteristics of key actions in fencing techniques using motion capture and biomechanical analysis technology, aiming to provide scientific evidence for athlete training and performance. The work combines eight infrared high-speed cameras with the Delsys surface Electromyography system for synchronized analysis, making an innovative contribution to the biomechanical research of fencing techniques. This technological combination allows for more precise tracking of an athlete`s three-dimensional movement trajectories and muscle activation, and offers new perspectives and more accurate guidance for training. The results are as follows. (1) During the forward lunge step, the integrated electromyographic activity of the deltoid muscle significantly increases (152.55 µV·s, p = 0.045), indicating a higher demand for arm stability in this movement. There are no significant differences in the activation levels of the biceps brachii and triceps brachii. The activation of the forearm muscles, specifically the extensor carpi radialis longus and extensor carpi radialis brevis, is significantly enhanced, at 81.61 µV·s (p = 0.047) and 98.72 µV·s (p = 0.049), respectively. For the lower limbs, the activation of the tibialis anterior muscle significantly increases (110.34 µV·s, p = 0.000). The activation of the gastrocnemius medialis and gastrocnemius lateralis also significantly enhances, with values of 53.22 µV·s (p = 0.001) and 35.75 µV·s (p = 0.000), respectively. The contribution of the deltoid muscle significantly increases to 31.2%, while the tibialis anterior muscle contribution increases to 26.5%. (2) The work also compares muscle activity, movement characteristics, and biomechanical parameters across athletes of different skill levels (beginner, intermediate, and advanced). The results show that the beginner group has the highest electromyography activity intensity (45.2 ± 5.1 µV), while the advanced group has the lowest (32.5 ± 3.8 µV). The movement trajectory stability is 12.3 ± 2.1 mm/s for the beginner group and 6.5 ± 1.2 mm/s for the advanced group. These results suggest that advanced athletes exhibit higher training effects in muscle activation efficiency and energy economy. These findings provide important theoretical support for optimizing fencing training methods and improving athletic performance.